Extraction and Characterization of Essential Oil of Rosa gruss-an-teplitz - MUMTAZ, WASEEM; MUKHTAR, HAMID; ANWAR, FAROOQ; NADEEM, RAZYIA (Asian Journal of Chemistry, 2010)
In present studies, the authors characterize the essential oil of Rosa gruss-an-teplitz. For this purpose, flower petals of Rosa gruss-an-telitz (surkha gulab) were collected. The physico-chemical properties and gas chromatographic analysis was also conducted. Data regarding the yield indicates that Rosa gruss-an-teplitz showed a yield of concrete oil and absolute oil 0.6851 and 0.3425 %, respectively. Various physico-chemical properties of yellowish, brown oil have been reported. Gas chromatogram of essential oil of Rosa grussan-teplitz detected some major compounds such as geraniol, linalool, phenethyl alcohol, benzaldehyde, citronellyl acetate, benzyl alcohol, geranyl acetate, etc. with different percentages.